Tick-borne encephalitis virus inhibits rRNA synthesis and host protein production in human cells of neural origin - Selinger, Martin (Jihočeská univerzita, 2020)
Tick-borne encephalitis virus (TBEV), a member of the genus Flavivirus (Flaviviridae), is a causative agent of a severe neuroinfection. Recently, several flaviviruses have been shown to interact with host protein synthesis. In order to determine whether TBEV interacts with this host process in its natural target cells, we analysed de novo protein synthesis in a human cell line derived from cerebellar medulloblastoma (DAOY HTB-186). We observed a significant decrease in the rate of host protein synthesis, including the housekeeping genes HPRT1 and GAPDH and the known interferon-stimulated gene viperin. In addition, TBEV infection resulted in a specific decrease of RNA polymerase I transcripts, 18S and 28S rRNAs and their precursor, 45-47S pre-rRNA, but had no effect on the RNA polymerase III-transcribed 5S rRNA levels.
Tick-borne encephalitis virus inhibits rRNA synthesis and host protein production in human cells of neural origin
Keywords: tick-borne encephalitis; host response; rRNA; transcriptional/translational shut-off; tick-borne encephalitis; host response; rRNA; transcriptional/translational shut-off